Inventory Valuation Method Selection and Earnings Quality: A Case From Indonesia’s Manufacturing Sector - Jovanna Darrena Untung; Yehezkiel Patarimankasih Agustinus Valentino Sianturi; Lindrianasari (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The selection of inventory valuation methods represents a critical accounting policy decision that directly influences reported earnings, particularly in manufacturing firms, where inventory constitutes a substantial portion of current assets. In the Indonesian context, PSAK 14 permits the use of either the FIFO or weighted average method, while explicitly prohibiting LIFO. This research aims to analyze the effect of inventory valuation method selection on earnings quality in manufacturing companies during the 2020–2024 period. This study compares companies applying the FIFO method and those applying the weighted average method to examine their impact on earnings quality. This research employs a quantitative approach using secondary data derived from the annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Earnings quality is measured using the accrual quality model by regressing total current accruals on past, current, and future operating cash flows for the 2020–2024 period. The results show that inventory valuation methods are associated with variations in accrual estimation patterns across firms. The findings also show that cost of goods sold (COGS) volatility and inventory intensity reflect operational characteristics that may influence the stability of financial reporting. Overall, the results suggest that inventory accounting practices in Indonesian manufacturing companies operate within a relatively consistent reporting environment, in which the reliability of earnings remains stable across firms applying different inventory valuation approaches.